Modified nanocellulose reinforced biodegradable composite films and methods of making the same
Patent Information
- Application Number
- CN202410931374.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-12
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-07-12
AI Technical Summary
然而,纤维素纳米晶表面羟基会促使纤维素纳米晶发生自聚集,在聚酯基体中容易发生团聚,此外高亲水性特性使其与疏水性生物聚酯基体不相容,进一步限制了纤维素纳米晶在基体中的均匀分散
(1)本发明使用的改性纳米纤维素在制备方面具有原料来源广、制备工艺简单、能耗低、可降解等优势,在结构方面具有高结晶度、高比表面积和重量轻等优点,可广泛作为优异增强剂;
Smart Images

Figure CN118994666B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of biodegradable composite membrane technology, specifically relating to a modified nanocellulose-reinforced biodegradable composite membrane and its preparation method. Background Technology
[0002] Petroleum-based synthetic plastics are widely used in various plastic film products due to their suitable functional properties. However, their non-degradability causes pollution that directly or indirectly affects the global carbon cycle, biodiversity, and ecosystem stability. One of the most effective solutions is to develop biodegradable, eco-friendly materials to reduce environmental impact and replace petroleum-based plastics. Therefore, there is an urgent need in fields such as agricultural mulch films and food packaging for a biodegradable composite film material that is simple to prepare, low in cost, and has excellent performance.
[0003] Polylactic acid (PLA) is a linear polyester polymerized from lactic acid. It is a fully biodegradable material with immense application potential in biomedicine, tissue engineering, and packaging materials. However, PLA's slow crystallization rate, low crystallinity, poor impact resistance, and low elongation at break limit its further promotion and application, often requiring modification during molding. Polypropylene carbonate (PPC) is a biodegradable polymer with advantages such as high elongation at break and good flexibility. Furthermore, its synthesis uses propylene oxide and the greenhouse gas CO2 as raw materials, mitigating the greenhouse effect and white pollution. Blending PLA with PPC can improve PLA's crystallinity and toughness. However, due to the significant difference in polarity between PLA and PPC, they are only partially compatible. Poor compatibility significantly reduces the overall mechanical properties of the material. Therefore, improving PLA's crystallinity while ensuring good compatibility is crucial for PLA material modification.
[0004] Cellulose nanocrystals (CNCs) are among the most promising nanomaterials, possessing excellent rigidity, adjustable aspect ratio, abundant hydroxyl groups, and renewability. They are widely used as reinforcing fillers and compatibilizers for PLA and PPC. However, the hydroxyl groups on the surface of cellulose nanocrystals can promote self-aggregation, leading to agglomeration in polyester matrices. Furthermore, their high hydrophilicity makes them incompatible with hydrophobic biopolyester matrices, further limiting the uniform dispersion of cellulose nanocrystals within the matrix. Summary of the Invention
[0005] Based on the aforementioned shortcomings and deficiencies in the prior art, one of the objectives of this invention is to at least solve one or more of the aforementioned problems in the prior art. In other words, one of the objectives of this invention is to provide a modified nanocellulose-reinforced biodegradable composite membrane and its preparation method that meet one or more of the aforementioned requirements.
[0006] To achieve the above-mentioned objectives, the present invention adopts the following technical solution: A method for preparing a modified cellulose nanofiber-reinforced biodegradable composite membrane includes the following steps: (1) Disperse nano-sized microcrystalline cellulose in an aqueous solution of sodium periodate and react at 60-80℃ for 50-60 min. Cool the reaction product to room temperature, wash and dry to obtain nano-cellulose containing aldehyde groups. (2) Disperse aldehyde-containing nanocellulose in deionized water, adjust the pH value to 4-5, add dodecanediamine, and react the mixture at 20-40℃ for 20-30h. Cool the reaction product to room temperature, wash and dry to obtain modified nanocellulose. (3) Polylactic acid and polypropylene carbonate are mixed and dissolved in chloroform to obtain a mixed solution. Modified nanocellulose is dispersed in chloroform to obtain a dispersion. The mixed solution and the dispersion are stirred and mixed to obtain a film-forming solution. The film-forming solution is cast and coated, and dried to obtain a biodegradable composite film.
[0007] This invention uses hydrophobically modified nanocellulose as a reinforcing agent and compatibilizer to improve the compatibility of PLA and PPC and the crystallization properties of PLA. Dodecanediamine (DDA) is used as the hydrophobic modifier. DDA is a long-chain alkylamine with relatively long hydrophobic alkyl chains. When DDA reacts with nanocellulose, the number of hydrophobic alkyl chains formed is relatively large, while the number of hydrogen bonds generated is relatively small. Therefore, the product contains more hydrophobic groups, and the molecules tend to repel water, thus making the modified cellulose nanocrystals exhibit hydrophobicity. Therefore, this invention uses DDA as a hydrophobically modified reinforcing agent and compatibilizer to prepare a reinforced and toughened biodegradable PLA / PPC composite film, which can be applied in fields such as biodegradable food packaging and agricultural films.
[0008] As a preferred embodiment, in step (2), the mass ratio of aldehyde-containing nanocellulose to dodecanediamine is 1:(1-3).
[0009] As a preferred embodiment, in step (3), the mass ratio of polylactic acid to polypropylene carbonate is (60-70):(30-40).
[0010] As a preferred embodiment, in step (3), the mass ratio of polylactic acid, polypropylene carbonate and chloroform is 1:(2-4), and the mixture is heated to 50-60°C and stirred to dissolve.
[0011] As a preferred embodiment, in step (3), the mass ratio of modified nanocellulose to chloroform in the dispersion is 1:(80-200).
[0012] As a preferred embodiment, the mass ratio of the nano-sized microcrystalline cellulose to the sodium periodate aqueous solution is 1:(90-110).
[0013] As a preferred embodiment, the concentration of the sodium periodate aqueous solution is 0.5–1 M.
[0014] The present invention also provides a modified nanocellulose-reinforced biodegradable composite membrane prepared by the preparation method described in any of the preceding embodiments.
[0015] As a preferred embodiment, the modified nanocellulose accounts for 1-5 wt% of the biodegradable composite membrane.
[0016] As a preferred option, biodegradable composite films are used as mulch films or food packaging.
[0017] Compared with the prior art, the beneficial effects of this invention are: (1) The modified nanocellulose used in this invention has advantages in terms of preparation, such as wide availability of raw materials, simple preparation process, low energy consumption and biodegradability. In terms of structure, it has advantages such as high crystallinity, high specific surface area and light weight, and can be widely used as an excellent reinforcing agent. (2) The biodegradable composite film of the present invention uses a simple casting coating preparation method, mature process, and easy mass production; the composite film has the advantages of good biocompatibility and high degradation rate, especially the strength reaches 34.9 MPa, the elongation at break reaches 46.9%, and it has significant improvements in crystallization ability and hydrophobic properties. It can replace the traditional petroleum-based plastic film and some similar biodegradable plastic films on the market to a certain extent. It can be used in fields such as mulch film and food packaging. There is a large market demand and considerable social and economic benefits. Attached Figure Description
[0018] Figure 1 This is a field emission scanning electron microscope image of the modified nanocellulose of Example 2 of the present invention; Figure 2 The infrared spectrum of the modified nanocellulose in Example 2 of this invention; Figure 3 This is a comparison chart of the contact angle test results of modified nanocellulose and nanocellulose in Example 2 and Comparative Example 1 of the present invention. Figure 4 These are mechanical tensile test diagrams of the composite films in various embodiments and comparative examples of the present invention; Figure 5 These are contact angle test diagrams of the composite films in various embodiments of the present invention. Detailed Implementation
[0019] The technical solution of the present invention will be further explained and illustrated below through specific embodiments.
[0020] Example 1: The composite membrane P in this embodiment 70 / P 30 The preparation method includes the following steps: (1) Disperse 1 part by mass of nano-sized microcrystalline cellulose MCC in 10.69 parts by mass of sodium periodate aqueous solution (concentration 0.5M), react at 60℃ for 60 min, and after the reaction is completed, cool to room temperature, wash and dry to obtain aldehyde-containing nano-cellulose CNC; (2) The mass ratio of polylactic acid (PLA) to polypropylene carbonate (PPC) is 70:30, and the mass ratio of PLA, PPC, and chloroform solution is 1:6. The PLA / PPC chloroform mixture is stirred and dissolved at 60°C. The dissolved PLA / PPC chloroform mixture is stirred at room temperature for 24 hours until fully dispersed. The PLA / PPC chloroform mixture is then cast and dried in an oven at 35°C for 48 hours to obtain a reinforced, toughened, and biodegradable composite film, abbreviated as P. 70 / P 30 .
[0021] Example 2: The preparation method of the composite membrane 1% CNC-DDA in this embodiment includes the following steps: (1) Disperse 1 part by mass of nano-sized microcrystalline cellulose MCC in 10.69 parts by mass of sodium periodate aqueous solution (concentration 0.5M), react at 60℃ for 60 min, and after the reaction is completed, cool to room temperature, wash and dry to obtain aldehyde-containing nano-cellulose CNC; (2) Disperse 1 part by mass of nanocellulose in deionized water and adjust the pH value to 4.5. Add 2 parts by mass of dodecanediamine and react the mixture at 30°C for 24 h. Cool the reaction product to room temperature, wash until neutral, and dry to obtain modified nanocellulose CNC-DDA. (3) The mass ratio of polylactic acid and polypropylene carbonate is 70:30, and the mass ratio of polylactic acid, polypropylene carbonate and chloroform solution is 1:4. The mixture is stirred and dissolved under the condition of heating to 60°C to obtain a polylactic acid / polypropylene carbonate chloroform mixture. The modified nanocellulose and chloroform were mixed at a mass ratio of 1:200, and the resulting dispersion was sonicated until uniformly dispersed. The polylactic acid / polypropylene carbonate chloroform mixture and the modified nanocellulose chloroform dispersion were then mixed and stirred at room temperature for 24 hours until fully dispersed. The PLA / PPC / CNC-DDA chloroform solution was then cast and coated, and dried in an oven at 35°C for 48 hours to obtain a reinforced, toughened, and biodegradable composite film, abbreviated as 1%CNC-DDA. The modified nanocellulose CNC-DDA constituted 1% of the total mass of the composite film.
[0022] Example 3: The preparation method of the composite membrane 3% CNC-DDA in this embodiment includes the following steps: (1) Disperse 1 part by mass of nano-sized microcrystalline cellulose MCC in 10.69 parts by mass of sodium periodate aqueous solution (concentration 0.5M), react at 60℃ for 60 min, and after the reaction is completed, cool to room temperature, wash and dry to obtain aldehyde-containing nano-cellulose CNC; (2) Disperse 1 part by mass of nanocellulose in deionized water and adjust the pH value to 4.5. Add 2 parts by mass of dodecanediamine and react the mixture at 30°C for 24 h. Cool the reaction product to room temperature, wash until neutral, and dry to obtain modified nanocellulose CNC-DDA. (3) The mass ratio of polylactic acid and polypropylene carbonate is 70:30, and the mass ratio of polylactic acid, polypropylene carbonate and chloroform solution is 1:3.09. The mixture is stirred and dissolved under the condition of heating to 60°C to obtain a polylactic acid / polypropylene carbonate chloroform mixture. The mass ratio of modified nanocellulose to chloroform in the dispersion was 1:100. The resulting dispersion was ultrasonicated until it was uniformly dispersed. The polylactic acid / polypropylene carbonate chloroform mixture and the modified nanocellulose chloroform dispersion were mixed and stirred at room temperature for 24 hours until fully dispersed. The PLA / PPC / CNC-DDA chloroform solution was then cast and dried in an oven at 35°C for 48 hours to obtain a composite film, abbreviated as 3% CNC-DDA. The modified nanocellulose (CNC-DDA) was required to account for 3% of the total mass of the composite film.
[0023] Example 4: The preparation method of the composite membrane 5% CNC-DDA in this embodiment includes the following steps: (1) Disperse 1 part by mass of nano-sized microcrystalline cellulose MCC in 10.69 parts by mass of sodium periodate aqueous solution (concentration 0.5M), react at 60℃ for 60 min, and after the reaction is completed, cool to room temperature, wash and dry to obtain aldehyde-containing nano-cellulose CNC; (2) Disperse 1 part by mass of nanocellulose in deionized water and adjust the pH value to 4.5. Add 2 parts by mass of dodecanediamine and react the mixture at 30°C for 24 h. Cool the reaction product to room temperature, wash until neutral, and dry to obtain modified nanocellulose CNC-DDA. (3) The mass ratio of polylactic acid and polypropylene carbonate is 70:30, and the mass ratio of polylactic acid, polypropylene carbonate and chloroform solution is 1:2. The mixture is stirred and dissolved under the condition of heating to 60°C to obtain a polylactic acid / polypropylene carbonate chloroform mixture. The mass ratio of modified nanocellulose to chloroform in the dispersion was 1:80. The resulting dispersion was ultrasonicated until it was uniformly dispersed. The polylactic acid / polypropylene carbonate chloroform mixture and the modified nanocellulose chloroform dispersion were mixed and stirred at room temperature for 24 hours until fully dispersed. The PLA / PPC / CNC-DDA chloroform solution was then cast and dried in an oven at 35°C for 48 hours to obtain a composite film, abbreviated as 5% CNC-DDA. The modified nanocellulose (CNC-DDA) was required to account for 5% of the total mass of the composite film.
[0024] Comparative Example 1: The preparation method of the composite membrane with 3% CNC-PEI in this embodiment includes the following steps: (1) Disperse 1 part by mass of nano-sized microcrystalline cellulose MCC in 10.69 parts by mass of sodium periodate aqueous solution (concentration 0.5M), react at 60℃ for 60 min, and after the reaction is completed, cool to room temperature, wash and dry to obtain aldehyde-containing nano-cellulose CNC; (2) Disperse 1 part by mass of aldehyde-containing nanocellulose in deionized water, adjust the pH value to 4.5, add 2 parts by mass of polyethyleneimine, react at 50°C for 24 h, after the reaction is completed, cool to room temperature, centrifuge, wash and dry to obtain modified nanocellulose CNC-PEI; (3) The mass ratio of polylactic acid and polypropylene carbonate is 70:30, and the mass ratio of polylactic acid, polypropylene carbonate and chloroform solution is 1:3.09. The mixture is stirred and dissolved under the condition of heating to 60°C to obtain a polylactic acid / polypropylene carbonate chloroform mixture. The mass ratio of modified nanocellulose to chloroform in the dispersion was 1:100. The resulting dispersion was ultrasonicated until it was uniformly dispersed. The polylactic acid / polypropylene carbonate chloroform mixture and the modified nanocellulose chloroform dispersion were mixed and stirred at room temperature for 24 hours until fully dispersed. The PLA / PPC / CNC-PEI chloroform solution was then cast and dried in an oven at 35°C for 48 hours to obtain a composite film, abbreviated as 3% CNC-PEI. The modified nanocellulose CNC-PEI accounted for 3% of the total mass of the composite film.
[0025] like Figure 1 As shown, the modified nanocellulose grafted with dodecanediamine in Example 2 still exhibits a spherical shape. The modified nanocellulose obtained in other examples is the same as in Example 2.
[0026] like Figure 2 The infrared spectrum shown indicates that the nanocellulose CNC is at 1732 cm⁻¹. -1 A distinct aldehyde C=O absorption peak was observed, while the aldehyde absorption peak almost disappeared in the infrared spectrum of modified nanocellulose CNC-DDA, and only reached 1644 cm⁻¹.-1 A new absorption peak appeared, originating from the CN stretching vibration, indicating a Schiff base reaction between the amino group of the dodecanediamine and the aldehyde group on the nanocellulose. Furthermore, it was observed that after the addition of dodecanediamine (DDA), the saturated CH bond in the CNC of the nanocellulose became two saturated CH bonds. This is because the aldehyde group and the amino group underwent an addition reaction, transforming the original single saturated CH bond into two new chemical bonds. These infrared results demonstrate the successful grafting of dodecanediamine onto nanocellulose.
[0027] Figure 3 Contact angle tests showed that CNC-DDA exhibited a significantly improved contact angle. This is because DDA is a long-chain alkylamine, typically possessing a relatively long hydrophobic alkyl chain. When DDA reacts with the aldehyde group of nanocellulose, the resulting product contains a relatively large number of hydrophobic alkyl chains and a relatively small number of hydrogen bonds, leading to an overall more hydrophobic property. Due to the increased number of hydrophobic groups, the molecule tends to repel water, thus exhibiting hydrophobicity. In contrast, CNC-PEI exhibits hydrophilicity because the reaction between the imine group in polyethyleneimine and the aldehyde group results in a product with more hydroxyl and amine (amide) functional groups. These functional groups increase hydrogen bonding between the molecule's surface and water molecules, thereby enhancing its hydrophilicity. Furthermore, the amine groups in the resulting product can also form hydrogen bonds with water molecules, further strengthening the interaction with water molecules and resulting in better hydrophilicity.
[0028] Figure 4 Tensile test results show that the composite membrane with modified nanocellulose exhibits significantly improved mechanical properties and elongation at break, with the 3% CNC-DDA membrane reaching a strength of 34.9 MPa, compared to P. 70 / P 30 The composite film showed a 78.9% increase in strength and a 46.9% increase in elongation at break, representing a relative increase of 31.3%. This demonstrates that modified nanocellulose provides additional benefits to the mechanical properties by improving the system's compatibility, making it suitable for use as mulch film or food packaging. The 5% CNC-DDA film exhibited lower strength and elongation at break than the P film. 70 / P 30 The composite membrane was damaged because the high concentration of modified nanocellulose caused it to agglomerate, which reduced its mechanical properties. The poor mechanical properties of 3% CNC-PEI were due to the incompatibility between the highly hydrophilic modified nanocellulose and the hydrophobic biopolyester matrix, which further restricted the uniform dispersion of cellulose nanocrystals in the matrix.
[0029] Figure 5 The contact angle test results show that the hydrophobic properties of the composite membrane after adding modified nanocellulose were greatly improved, thanks to the successful preparation of hydrophobic modified nanocellulose.
[0030] Given that there are numerous embodiments of the present invention, and the raw materials and quantities involved can be selected within a limited range according to actual needs, and that the experimental data for each embodiment are extensive and numerous, it is not suitable to list and describe them one by one here. However, the content to be verified and the final conclusions obtained in each embodiment are similar. Therefore, the verification content of each embodiment will not be described one by one here.
[0031] The above description is merely a detailed explanation of preferred embodiments and principles of the present invention. For those skilled in the art, there may be changes in specific implementation methods based on the ideas provided by the present invention, and these changes should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a modified nanocellulose-reinforced biodegradable composite membrane, characterized in that, Includes the following steps: (1) Disperse nano-sized microcrystalline cellulose in an aqueous sodium periodate solution and react at 60-80℃ for 50-60 min. Cool the reaction product to room temperature, wash and dry to obtain nano-cellulose containing aldehyde groups. (2) Disperse aldehyde-containing nanocellulose in deionized water, adjust the pH value to 4-5, add dodecanediamine, and react the mixture at 20-40℃ for 20-30h. Cool the reaction product to room temperature, wash and dry to obtain modified nanocellulose. (3) Polylactic acid and polypropylene carbonate are mixed and dissolved in chloroform to obtain a mixed solution. Modified nanocellulose is dispersed in chloroform to obtain a dispersion. The mixed solution and the dispersion are stirred and mixed to obtain a film-forming solution. The film-forming solution is cast and coated, and dried to obtain a biodegradable composite film. In step (2), the mass ratio of aldehyde-containing nanocellulose to dodecanediamine is 1:(1-3). In step (3), the mass ratio of polylactic acid to polypropylene carbonate is (60-70):(30-40). In step (3), the mass ratio of modified nanocellulose to chloroform in the dispersion is 1:(80-200).
2. The preparation method according to claim 1, characterized in that, In step (3), the mass ratio of polylactic acid, polypropylene carbonate and chloroform is 1:(2-4), and the mixture is heated to 50-60°C and stirred to dissolve.
3. The preparation method according to claim 1, characterized in that, The mass ratio of the nano-sized microcrystalline cellulose to the sodium periodate aqueous solution is 1:(90-110), and the concentration of the sodium periodate aqueous solution is 0.5-1M.
4. The modified nanocellulose-reinforced biodegradable composite membrane prepared by the preparation method according to any one of claims 1-3.
5. The biodegradable composite membrane according to claim 4, characterized in that, The modified nanocellulose accounts for 1-5 wt% of the biodegradable composite membrane.
6. The biodegradable composite membrane according to claim 4 or 5, characterized in that, Used as mulch film or food packaging.
Citation Information
Patent Citations
Modified nanocellulose as well as preparation method and application thereof
CN108219009A
High-transparency and high-strength nanocellulose flexible film as well as preparation method and application thereof
CN113402745A
